Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve this problem, we need to refer to the principles of vector addition of forces and the law of cosines in order to find the angle [tex]\(\beta\)[/tex] between the two forces. Let's break down the steps:
### Step 1: Resultant of Initial Forces
Given two forces [tex]\( F_1 = 3 \, \text{N} \)[/tex] and [tex]\( F_2 = 4 \, \text{N} \)[/tex] at an angle [tex]\(\beta\)[/tex], the resultant [tex]\( R \)[/tex] can be calculated using the law of cosines:
[tex]\[ R = \sqrt{F_1^2 + F_2^2 + 2 F_1 F_2 \cos(\beta)} \][/tex]
Substitute [tex]\( F_1 \)[/tex] and [tex]\( F_2 \)[/tex]:
[tex]\[ R = \sqrt{3^2 + 4^2 + 2 \cdot 3 \cdot 4 \cos(\beta)} \][/tex]
[tex]\[ R = \sqrt{9 + 16 + 24 \cos(\beta)} \][/tex]
[tex]\[ R = \sqrt{25 + 24 \cos(\beta)} \][/tex]
### Step 2: New Forces and New Resultant
Now, the forces are increased:
[tex]\[ F_1' = F_1 + 9 = 3 + 9 = 12 \, \text{N} \][/tex]
[tex]\[ F_2' = F_2 + 12 = 4 + 12 = 16 \, \text{N} \][/tex]
The new resultant [tex]\( R' \)[/tex] is given as being four times the original resultant [tex]\( R \)[/tex]:
[tex]\[ R' = 4 R \][/tex]
Using the law of cosines for the new forces:
[tex]\[ R' = \sqrt{F_1'^2 + F_2'^2 + 2 F_1' F_2' \cos(\beta)} \][/tex]
Substitute [tex]\( F_1' \)[/tex] and [tex]\( F_2' \)[/tex]:
[tex]\[ R' = \sqrt{12^2 + 16^2 + 2 \cdot 12 \cdot 16 \cos(\beta)} \][/tex]
[tex]\[ R' = \sqrt{144 + 256 + 384 \cos(\beta)} \][/tex]
[tex]\[ R' = \sqrt{400 + 384 \cos(\beta)} \][/tex]
### Step 3: Relationship Between Original and New Resultants
Given [tex]\( R' = 4R \)[/tex]:
[tex]\[ \sqrt{400 + 384 \cos(\beta)} = 4 \sqrt{25 + 24 \cos(\beta)} \][/tex]
Square both sides to eliminate the square roots:
[tex]\[ 400 + 384 \cos(\beta) = 16 (25 + 24 \cos(\beta)) \][/tex]
[tex]\[ 400 + 384 \cos(\beta) = 400 + 384 \cos(\beta) \][/tex]
Simplify the equation:
[tex]\[ 400 + 384 \cos(\beta) = 400 + 384 \cos(\beta) \][/tex]
This equation holds true, which means our assumed [tex]\(\beta\)[/tex] (a consistent angle that satisfies the relation) must be correct. However, for the algebraic check; we should solve for [tex]\(\cos(\beta)\)[/tex].
### Step 4: Solve for [tex]\(\cos(\beta)\)[/tex]
Rearrange and isolate one term on each side:
[tex]\[ 384 \cos(\beta) = 384 \cos(\beta) \][/tex]
Since the equation is consistent this means [tex]\(\beta\)[/tex] could potentially be solved with the positions where such conversions hold.
### Conclusion
### Conclusion
The angle β should satisfies [tex]\(\beta = \Box). To find the exact symbolic Solution is simple once both equivalent representations are deduced yielding: \(\beta \approx 90^{\circ}\)[/tex]
### Step 1: Resultant of Initial Forces
Given two forces [tex]\( F_1 = 3 \, \text{N} \)[/tex] and [tex]\( F_2 = 4 \, \text{N} \)[/tex] at an angle [tex]\(\beta\)[/tex], the resultant [tex]\( R \)[/tex] can be calculated using the law of cosines:
[tex]\[ R = \sqrt{F_1^2 + F_2^2 + 2 F_1 F_2 \cos(\beta)} \][/tex]
Substitute [tex]\( F_1 \)[/tex] and [tex]\( F_2 \)[/tex]:
[tex]\[ R = \sqrt{3^2 + 4^2 + 2 \cdot 3 \cdot 4 \cos(\beta)} \][/tex]
[tex]\[ R = \sqrt{9 + 16 + 24 \cos(\beta)} \][/tex]
[tex]\[ R = \sqrt{25 + 24 \cos(\beta)} \][/tex]
### Step 2: New Forces and New Resultant
Now, the forces are increased:
[tex]\[ F_1' = F_1 + 9 = 3 + 9 = 12 \, \text{N} \][/tex]
[tex]\[ F_2' = F_2 + 12 = 4 + 12 = 16 \, \text{N} \][/tex]
The new resultant [tex]\( R' \)[/tex] is given as being four times the original resultant [tex]\( R \)[/tex]:
[tex]\[ R' = 4 R \][/tex]
Using the law of cosines for the new forces:
[tex]\[ R' = \sqrt{F_1'^2 + F_2'^2 + 2 F_1' F_2' \cos(\beta)} \][/tex]
Substitute [tex]\( F_1' \)[/tex] and [tex]\( F_2' \)[/tex]:
[tex]\[ R' = \sqrt{12^2 + 16^2 + 2 \cdot 12 \cdot 16 \cos(\beta)} \][/tex]
[tex]\[ R' = \sqrt{144 + 256 + 384 \cos(\beta)} \][/tex]
[tex]\[ R' = \sqrt{400 + 384 \cos(\beta)} \][/tex]
### Step 3: Relationship Between Original and New Resultants
Given [tex]\( R' = 4R \)[/tex]:
[tex]\[ \sqrt{400 + 384 \cos(\beta)} = 4 \sqrt{25 + 24 \cos(\beta)} \][/tex]
Square both sides to eliminate the square roots:
[tex]\[ 400 + 384 \cos(\beta) = 16 (25 + 24 \cos(\beta)) \][/tex]
[tex]\[ 400 + 384 \cos(\beta) = 400 + 384 \cos(\beta) \][/tex]
Simplify the equation:
[tex]\[ 400 + 384 \cos(\beta) = 400 + 384 \cos(\beta) \][/tex]
This equation holds true, which means our assumed [tex]\(\beta\)[/tex] (a consistent angle that satisfies the relation) must be correct. However, for the algebraic check; we should solve for [tex]\(\cos(\beta)\)[/tex].
### Step 4: Solve for [tex]\(\cos(\beta)\)[/tex]
Rearrange and isolate one term on each side:
[tex]\[ 384 \cos(\beta) = 384 \cos(\beta) \][/tex]
Since the equation is consistent this means [tex]\(\beta\)[/tex] could potentially be solved with the positions where such conversions hold.
### Conclusion
### Conclusion
The angle β should satisfies [tex]\(\beta = \Box). To find the exact symbolic Solution is simple once both equivalent representations are deduced yielding: \(\beta \approx 90^{\circ}\)[/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.